Synthesis of 4,7,9-Trihydroxy[1]benzofuro[3,2-d]pyrimidine-6-carboxamide: Evaluation of Cytotoxicity and Inhibition of Protein Kinase C (CaPkc1) - Dao Viet Hung; Tran Khac Vu (Journal of Chemistry)
The protein kinase Pkc1 of Candida albicans (CaPkc1), one of the key proteins involved in MAPK pathway, is described as a regulator of cell wall integrity during growth, morphogenesis, and response to cell wall stress. The (–)-cercosporamide is an antifungal natural product isolated from the phytopathogen fungus Cercosporidium henningsii. This phytoxin was found to inhibit selectively CaPkc1 and constitutes an interesting model for the design of novel antifungal molecules. In this research, 4,7,9-trihydroxy[1]benzofuro[3,2-d]pyrimidine-6-carboxamide (13) derived from (–)-cercosporamide was synthesized via a seven-step procedure by well-known reactions and evaluation of cytotoxicity and inhibition of CaPkc1. The bioassay showed CaPkc1 inhibitory activity 87% higher and cytotoxicity 100 times less than the reference, (–)-cercosporamide.